Evidence for Effective Multiple K+-Current Inhibitions by Tolvaptan, a Non-peptide Antagonist of Vasopressin V2 Receptor - Lu, Te-Ling; Chang, Wei-Ting; Chan, Chee-Hong; Wu, Sheng-Nan (Frontiers in Pharmacology, 2019)
Tolvaptan (TLV), an oral non-peptide antagonist of vasopressin V2 receptor, has been increasingly used for managements in patients with hyponatremia and/or syndrome of inappropriate antidiuretic hormone secretion. However, none of the studies have thus far been investigated with regard to its possible perturbations on membrane ion currents in endocrine or neuroendocrine cells. In our electrophysiological study, the whole-cell current recordings showed that the presence of TLV effectively and differentially suppressed the amplitude of delayed rectifier K+ (IK(DR)) and M-type K+ current (IK(M)) in pituitary GH3 cells with an IC50 value of 6.42 and 1.91 M, respectively. This compound was also capable of shifting the steady-state activation curve of IK(M) to less depolarized potential without any appreciable change in the gating charge of this current. TLV at a concentration greater than 10 M also suppressed the amplitude of erg-mediated K+ current or the activity of large-conductance Ca2+-activated K+ channels; however, this compound failed to alter the amplitude of hyperpolarization-activated cation current in GH3 cells. In vasopressin-preincubated GH3 cells, TLV-mediated suppression of IK(M) remained little altered. Under current-clamp condition, we also observed that addition of TLV increased the firing of spontaneous action potentials in GH3 cells and further addition of flupirtine could reverse TLV-mediated elevation of the firing. In Madin-Darby canine kidney (MDCK) cells, the K+ current elicited by long ramp pulse was also effectively subject to inhibition by this compound. Findings from the present study were thus stated as saying that the suppression by TLV of multiple type K+ currents could be direct and independent of its antagonism of vasopressin V2 receptors. Our study also reveals an important aspect that should be considered when assessing aquaretic effect of TLV or its structurally similar compounds.